The transformations in the cerrado and of the relationship between man and nature in 200 years of August's Saint-Hilaire journey to Goiás: As transformações no cerrado e da relação homem/natureza nos 200 anos da viagem de August de Saint-Hilaire a Goiás (Brasil) (Revista de História da UEG (REVHIST), 2023)
In 2019 it was the 200th anniversary of August Saint-Hilaire's trip to Goiás, starting from this perspective, the objective of this article is to make an analysis, in the long-term historical perspective, of the transformations of the relationship between man and Nature in the Cerrado. The reflections and notes lead us to reflect that the dynamics of the historical process do not happen in the same rhythms and, however distant the communications between different peoples and cultures were, one could not speak of isolation. The interactions took place, but in different historical dynamic rhythms and the hegemonic dominance of urban, industrial, and capitalist culture will only be consolidated in Goiás after the construction and transfer of the federal capital to Brasilia in 1960.Keywords: History. Culture. Economy. Nature.